Optimalisasi Peningkatan Branding, Digital Marketing Dan Legalitas Usaha Bagi UMKM Keripik - Feronica, Maria; Agustin, Alifia Devi; Mufida, Laila; Setyawan, Rony; Sri Diyanti, Daffa Dwi (Yayasan Cendekia Gagayunan Indonesia, 2025)
The small-scale chip (keripik) entrepreneurs in Candiwatu Village, Pacet District, continue to face challenges related to business legality, branding, and digital marketing. This community service program aims to enhance the knowledge and skills of these micro, small, and medium enterprises (MSMEs) through assistance in obtaining Business Identification Numbers (NIB) and Home Industry Food Permits (PIRT), product branding training, and the use of social media and e-commerce for digital marketing. The implementation method adopts a participatory approach through observation, training, and intensive mentoring. The results indicate a significant improvement in the partners' understanding and business practices, such as the appearance of product labels, creation of digital business accounts, and active efforts in online product promotion. This program demonstrates that a digital-based empowerment strategy can effectively build MSME competitiveness in the era of digital transformation.